Respuesta :

qabtt

The distributive property says that the following is true:

[tex]a(b + c) = ab + ac[/tex]


In our problem, we will consider the term outside (or [tex]a[/tex] in the first equation) to be [tex](x + 3)[/tex] and we will consider the expression inside the parentheses to be [tex](x^2 - 2x + 4)[/tex]. To use the distributive property, we are going to apply the outside term to all terms within the second expression. This is represented as:

[tex](x + 3)(x^2) - (x + 3)(2x) + (x + 3)(4)[/tex]


We can now use the distributive property again to simplify the new expression:

[tex](x + 3)(x^2 - 2x + 4) = x^3 + 3x^2 - 2x^2 - 6x + 4x + 12 = x^3 + x^2 - 2x + 12[/tex]


The answer is x³ + x² - 2x + 12.

gmany

We multiply each monomial of the first parenthesis by each monomial of the second parenthesis:

[tex](x+3)(x^2-2x+4)\\\\=(x)(x^2)+(x)(-2x)+(x)(4)+(3)(x^2)+(3)(-2x)+(3)(4)[/tex]

Use [tex]a^n\cdot a^m=a^{n+m}[/tex]

[tex]=x^3-2x^2+4x+3x^2-6x+12[/tex]

combine like terms

[tex]=x^3+(-2x^2+3x^2)+(4x-6x)+12=x^3+x^2-2x+12[/tex]